Assessment of the knowledge acquisition process in Lithuanian insurance sector - Raudeliūnienė, Jurgita; Račinskaja, Irena (Business: Theory and Practice, 2014)
Under the development of favourable globalization conditions, the demand for and importance of knowledge in the insurance sector are rapidly growing, which is characterized by the variety of insurance services and offered products as well as by a permanent change in efforts to efficiently meet the needs of society. Therefore, knowledge is becoming a unique factor that leads to the increased exclusivity of the organization in this particular sector when the recently acquired knowledge helps the employees of the company with efficiently performing work activities and creating for consumer advantages that can be hardly imitated by other insurance organizations. However, the process of knowledge acquisition will be worthless without efficient instruments for assessing the procedures leading to obtaining the necessary knowledge on demand and time. Every insurance organization in Lithuania tries to acquire the necessary knowledge on time in the most convenient way; however, researchers and business representatives feel a lack of tools for assessing and improving the knowledge acquisition process. According to scientific literature, a lack of complexity evaluating the knowledge acquisition process creates a precondition for developing instruments for the assessment of this process. The object of research is the evaluation of the knowledge acquisition process in the organizations of Lithuanian insurance sector. The goal of the article is to offer an integrated instrument of the knowledge acquisition process for the organization working in Lithuanian insurance sector. To achieve this goal, the following tasks have been implemented: the analysis of the theoretical aspects of the factors and methods of the knowledge acquisition process; the establishment of the factors specific to organizations in Lithuanian insurance sector for the purposes of assessing the knowledge acquisition process; the identification of the problematic areas of the knowledge acquisition process regarding the insurance sector in Lithuania. According to the results of empirical research, an integrated assessment instrument for the knowledge ac quisition process has been proposed for the organizations of Lithuanian insurance sector in order to evaluate the effectiveness of the actions taken and to develop the proposals to improve the above introduced process. Žinių įgijimo proceso vertinimas Lietuvos draudimo sektoriuje Santrauka Besiplėtojančios globalizacijos sąlygomis ypač sparčiai auga žinių poreikis ir svarba draudimo sektoriuje, pasižyminčiame net tik draudimo paslaugų ir produktų įvairove, bet ir nuolatine jų kaita stengiantis kuo efektyviau patenkinti visuomenės poreikius. Todėl žinios tampa unikalumo veiksniu, lemiančiu šio sektoriaus organizacijų išskirtinumo didėjimą, kai įgytos žinios padeda organizacijų darbuotojams ne tik efektyviai atlikti darbinę veiklą, bet ir sukurti vartotojams tuos pranašumus, kuriuos būtų sudėtingiau imituoti kitoms draudimo organizacijoms. Žinių įgijimo procesas nebus vertingas, jeigu nebus efektyvių proceso vertinimo metodų, kas tiesiogiai siejasi su reikiamų žinių įgijimu pagal poreikį ir laiku. Kiekviena draudimo organizacija Lietuvoje stengiasi įgyti reikiamų žinių tinkamu metu ir patogiausiu būdu, tačiau mokslininkai ir verslo praktikai stokoja metodų ne tik žinių įgijimo procesui įvertinti, bet ir patobulinti. Mokslinėje literatūroje žinių įgijimo proceso vertinimo kompleksiškumo nebuvimas sudaro prielaidas sukurti šio proceso įvertinimo metodus. Šio tyrimo objektas – žinių įgijimo proceso vertinimas Lietuvos draudimo sektoriaus organizacijose. Šio straipsnio tikslas – pasiūlyti integruotą žinių įgijimo proceso vertinimo metodą Lietuvos draudimo sektoriaus organizacijoms. Tikslui pasiekti suformuoti šie uždaviniai: išanalizuoti žinių įgijimo proceso vertinimo veiksnių ir metodų teorinius aspektus; nustatyti žinių įgijimo proceso vertinimo veiksnius, būdingus Lietuvos draudimo sektoriaus organizacijoms; identifikuoti problemines Lietuvos draudimo sektoriaus žinių įgijimo proceso sritis. Remiantis atliktais empiriniais tyrimais buvo pasiūlytas integruotas žinių įgijimo proceso vertinimo metodas Lietuvos draudimo sektoriaus organizacijoms, sudarantis prielaidas įvertinti proceso efektyvumą ir formuoti proceso tobulinimo siūlymus. Reikšminiai žodžiai: draudimo sektorius, žinių įgijimas, vertinimas.